1992
DOI: 10.1177/000348949210100114
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of New Telescopic Video Microlaryngoscopic and Standard Microlaryngoscopic Techniques

Abstract: A new approach to microlaryngeal surgery using a specially designed video microlaryngoscope with a rigid endoscopic telescope and an attached video camera was introduced by Kantor et al in 1990. The ability to video document and perform surgery of the larynx by viewing a high-resolution television image was demonstrated. This method was recommended over the standard microscopic technique for increased visibility with greater depth of field, unimpeded instrument access, instant documentation, and superior teach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
2

Year Published

1999
1999
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 5 publications
0
9
0
2
Order By: Relevance
“…They have shown that the technique is not sufficient for evaluation of the ventricle, subglottic area, and anterior commissure. 17 Poels et al have compared the consistency of the preoperative and intraoperative diagnosis of 221 patients with benign vocal fold lesions. They used both halogen and stroboscopic light for the preoperative diagnosis and direct microscopic visualization for intraoperative diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…They have shown that the technique is not sufficient for evaluation of the ventricle, subglottic area, and anterior commissure. 17 Poels et al have compared the consistency of the preoperative and intraoperative diagnosis of 221 patients with benign vocal fold lesions. They used both halogen and stroboscopic light for the preoperative diagnosis and direct microscopic visualization for intraoperative diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Utilizando o segundo tipo de laringoscópio não obtiveram sucesso em 4,2% (1/24) dos pacientes, sendo o exame considerado difícil em outro paciente 20 . Na descrição do seu aparelho, Dedo alertou para as dificuldades da laringoscopia direta, relatando em seu trabalho a impossibilidade em 2,3% (2/85) dos pacientes.…”
Section: Discussionunclassified
“…The frames obtained have sufficient lighting and excellent clarity, as is consistent with the findings of others. 6,12 Our definition of a "successful visualization" took into account both the ability to obtain a recording of the full region of interest and the tolerance of patients to the procedure. If patient discomfort was too great, the telescopy would be immediately discontinued at the patient's request and the examination considered unsuccessful.…”
Section: Commentmentioning
confidence: 99%